Smartphone-Based Refractive Index Sensor Utilizing Gold Nanorod-Coated CD Grating - Isara Wongsaroj; Chokchai Puttharugsa; Nongluck Houngkamhang (Thai Journal of Nanoscience and Nanotechnology, 2024)
The refractive index measurement device utilizing a gold nanorod (GNR)-coated CD grating and operated through a smartphone has been developed and successfully demonstrated. The GNRs were synthesized using the seed-mediated growth method, with varying amounts of silver nitrate, specifically tailored for refractive index sensing applications. Due to their anisotropic shapes, GNRs exhibit two absorption peaks associated with localized surface plasmon resonance (LSPR). This study showcased the LSPR absorption sensitivity of GNRs to changes in solution refractive index. Solutions with diverse refractive index values were prepared and measured using the GNR-coated CD grating as the sensing material and a smartphone as the detector. The observed adsorption changes correlated directly with the refractive index of the solutions. Notably, the synthesized GNR-coated CD grating demonstrated a high sensitivity of 557.76 Green Intensity/RIU. Remarkably, this setup eliminates the need for traditional optical components such as lenses, filters, or apertures, relying solely on the smartphone's LED flash and camera. This work highlights the potential for portable, real-time, cost-effective, and easily deployable refractive index sensing devices.
Keywords: Advanced Fiber Optic Sensors; Optical Coatings and Gratings; Plasmonic and Surface Plasmon Research